Impact of preoperative muscle quality on postoperative severe complications after radical gastrectomy for gastric cancer patients - Ryota Matsui; Noriyuki Inaki; Toshikatsu Tsuji (Annals of Gastroenterological Surgery, 2021)
Abstract Background Preoperative sarcopenia is an important risk factor for postoperative complications in patients with gastric cancer. However, the relationship between muscle quality and postoperative complications in patients with gastric cancer is inadequately studied. Therefore, we investigated the impact of preoperative muscle quality on severe postoperative complications after radical gastrectomy. Methods A total of 840 patients who underwent radical gastrectomy for p‐stages I–III primary gastric cancer between April 2008 and June 2018 with preoperative computed tomography (CT) scans and body composition analysis were included. We measured intramuscular adipose tissue content (IMAC) as an indicator of muscle quality. A higher IMAC signified a poorer quality. All statistical analyses were performed with EZR, and a P‐value < 0.05 was considered statistically significant. Results The low‐IMAC and high‐IMAC groups had 422 (50.2%) and 418 (49.8%) patients, respectively. The latter were older (P < 0.001), had higher body mass index (BMI) (P < 0.001), and higher rates of chronic kidney disease (CKD) (P = 0.002) and diabetes (P < 0.001). They had lower skeletal muscle indexes (SMI) (P = 0.011) and higher visceral fat areas (VFA) (P < 0.001). They also experienced more intraoperative blood loss (P < 0.001) and greater complications (P = 0.016). Multivariate analysis showed that high‐IMAC was an independent risk factor for severe complications (odds ratio: 2.260, 95% confidence interval: 1.220‐4.190, P = 0.010). Conclusions Poor preoperative muscle quality is an independent risk factor for severe postoperative complications after radical gastrectomy in patients with gastric cancer.